Effects of Regulation on Methadone and Buprenorphine Provision in the Wake of Hurricane Sandy - McClure, Bridget (Springer US, 2014)
Hurricane Sandy led to the closing of many major New York City public hospitals including their substance abuse clinics and methadone programs, and the displacement or relocation of thousands of opioid-dependent patients from treatment. The disaster provided a natural experiment that revealed the relative strengths and weaknesses of methadone treatment in comparison to physician office-based buprenorphine treatment for opioid dependence, two modalities of opioid maintenance with markedly different regulatory requirements and institutional procedures. To assess these two modalities of treatment under emergency conditions, semi-structured interviews about barriers to and facilitators of continuity of care for methadone and buprenorphine patients were conducted with 50 providers of opioid maintenance treatment. Major findings included that methadone programs presented more regulatory barriers for providers, difficulty with dose verification due to impaired communication, and an over reliance on emergency room dosing leading to unsafe or suboptimal dosing. Buprenorphine treatment presented fewer regulatory barriers, but buprenorphine providers had little to no cross-coverage options compared to methadone providers, who could refer to alternate methadone programs. The findings point to the need for well-defined emergency procedures with flexibility around regulations, the need for a central registry with patient dose information, as well as stronger professional networks and cross-coverage procedures. These interventions would improve day-to-day services for opioid-maintained patients as well as services under emergency conditions.